Ablation of the Evolutionarily Acquired Functions of the Atp1b4 Gene Increases Metabolic Capacity and Reduces Obesity - Nikolai N. Modyanov; Lucia Russo; Sumona Ghosh Lester; Tamara R. Castañeda; Himangi G. Marathe; Larisa V. Fedorova; Raymond E. Bourey; Sonia M. Najjar; Ivana L. de la Serna (Life, 2025)
In placental mammals, the co-option of vertebrate orthologous ATP1B4 genes has profoundly altered the properties of the encoded BetaM proteins, which function as bona fide β-subunits of Na,K-ATPases in lower vertebrates. Eutherian BetaM acquired an extended Glu-rich N-terminal domain resulting in the complete loss of its ancestral function and became a skeletal and cardiac muscle-specific component of the inner nuclear membrane. BetaM is expressed at the highest level during perinatal development and is implicated in gene regulation. Here we report the long-term consequences of Atp1b4 ablation on metabolic parameters in adult mice. Male BetaM-deficient (Atp1b4−/Y) mice have remarkably lower body weight and adiposity than their wild-type littermates, despite higher food intake. Indirect calorimetry shows higher energy expenditure (heat production and oxygen consumption) with a greater spontaneous locomotor activity in Atp1b4−/Y males. Their lower respiratory exchange ratio suggests a greater reliance on fat metabolism compared to their wild-type counterparts. Consistently, Atp1b4−/Y KO mice exhibit enhanced β-oxidation in skeletal muscle, along with improved glucose and insulin tolerance. These robust metabolic changes induced by Atp1b4 disruption demonstrate that eutherian BetaM plays an important role in regulating adult mouse metabolism. This demonstrates that bypassing the co-option of Atp1b4 potentially reduces susceptibility to obesity. Thus, Atp1b4 ablation leading to the loss of evolutionarily acquired BetaM functions serves as a model for a potential alternative pathway in mammalian evolution.